A high refractive index cycloolefin copolymer and its preparation method and application

By preparing a high refractive index cyclic olefin copolymer of a specific general formula, the deficiencies of materials in the existing technology in terms of refractive index, light transmittance, heat resistance and processing performance are solved, and high refractive index and high light transmittance are achieved. Copolymer with good heat resistance and low birefringence, suitable for large-scale production.

CN118791657BActive Publication Date: 2025-01-21TOPOLEFIN TECHNOLOGY (QUZHOU) CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411276571.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-21
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

The existing cycloolefin copolymers have shortcomings in refractive index, light transmittance, heat resistance and processing properties, and cannot have both high refractive index and high light transmittance, heat resistance, low birefractive index and excellent processing. performance.

Method used

By preparing a high refractive index cyclic olefin copolymer whose general formula is a specific comonomer composition, using specific catalysts and cocatalysts, the copolymerization reaction is performed to obtain materials with high refractive index, light transmittance and heat resistance. .

Benefits of technology

A copolymer with high refractive index (1.55~1.64) and high transmittance (more than 90%) has been achieved, which has good heat resistance and low birefringence properties and is economically suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_6
    Figure SMS_6
  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of polymer synthesis, and discloses a high refractive index cycloolefin copolymer, and a preparation method, which is characterized by comprising the following steps: copolymerizing comonomer A, comonomer B and ethylene to obtain the high refractive index cycloolefin copolymer. The present invention also discloses the use of the high refractive index cycloolefin copolymer in the preparation of optical lenses / lenses, polarizing film, contact lenses or AR / VR. Compared with the prior art, the cycloolefin copolymer prepared by the present invention has a refractive index of 1.55-1.64, a transmittance of more than 90%, a glass transition temperature of 79-190°C, and a birefringence of no more than 25nm. It also has a higher refractive index, a higher transmittance, heat resistance, and a lower birefringence, and is economically suitable for scaled-up production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer synthesis, in particular to a high-refractive-index cycloolefin copolymer and a preparation method and application thereof. Background Art

[0002] Cyclic olefin copolymer (COC) refers to a polyolefin material with a cyclic structure in the main chain, which has high transparency, excellent heat resistance, chemical stability, low dielectric constant, good moisture barrier, etc. At present, cyclic olefin copolymer has been widely used in the manufacture of various optical lenses / lenses, polarizing films, contact lenses or AR / VR, electronic and electrical components, medicine, food packaging materials, etc.

[0003] Cyclic olefin copolymers are mainly obtained by copolymerizing ethylene and norbornene using metallocene catalysts, such as the APELTM series of cyclic olefin copolymers produced by Japan's Mitsui Company, which are mainly used in automotive cameras and head-mounted display (HMD) lenses.

[0004] However, for existing cycloolefin copolymers, on the one hand, the molecular chain rigidity of such cycloolefin copolymers is relatively strong and the elongation at break is relatively poor. On the other hand, the refractive index of such cycloolefin copolymers is fixed at 1.52~1.55. The inability to further increase the refractive index limits the application of such cycloolefin copolymers.

[0005] Existing cycloolefin copolymers cannot simultaneously possess high refractive index and high light transmittance, heat resistance, low birefringence and excellent processing properties. Summary of the invention

[0006] The first technical problem to be solved by the present invention is to provide a high refractive index cycloolefin copolymer having high refractive index and high light transmittance, heat resistance, low birefringence and excellent processing performance in view of the current status of the prior art.

[0007] The second technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned high refractive index cycloolefin copolymer.

[0008] The third technical problem to be solved by the present invention is to provide an application of the high refractive index cycloolefin copolymer.

[0009] The technical solution adopted by the present invention to solve the first technical problem is: a high refractive index cycloolefin copolymer, characterized by the general formula:

[0010] Formula I;

[0011] Wherein, R1, R2, R3, R4, R5, R6, R7, and R8 are hydrogen, substituted or unsubstituted C1~C 20Straight or branched alkyl, substituted or unsubstituted C3~C 20 Cycloalkyl, substituted or unsubstituted C6~C 30 Aryl, substituted or unsubstituted C3~C 20 One of heteroaryl, halogen or ester groups;

[0012] a is 0, 1 or 2;

[0013] The molar ratio of x, y, and z is (5~40%):(35~85%):(5~65%).

[0014] Preferably, R1, R2, R3, R4, R5, R6, R7, R8 are -H, -(CH2)n-R9, -(CH2)nOR 10 、-(CH2)nSR 11 、C1~C 12 Straight chain, C5~C 15 Cycloalkyl, C6~C 20 Aryl, C3~C 15 One of the heteroaryl groups or ester groups, n is an integer from 1 to 16;

[0015] Among them, R9, R 10 , R 11 It is one of hydrogen, biphenyl, naphthyl, carbazole, fluorenyl, acenaphthenyl, phenanthryl and diphenylamino.

[0016] Preferably, the high refractive index cycloolefin copolymer has a refractive index of 1.55-1.64, a light transmittance of more than 90%, a glass transition temperature of 79-190° C., and a birefringence of no more than 25 nm.

[0017] The technical solution adopted by the present invention to solve the second technical problem is: a method for preparing the above-mentioned high-refractive index cycloolefin copolymer, characterized by comprising the following steps: copolymerizing comonomer A, comonomer B and ethylene to obtain the high-refractive index cycloolefin copolymer;

[0018] The general formula of the comonomer A is:

[0019] Formula II;

[0020] Wherein, R1, R2, R3, and R4 are hydrogen, substituted or unsubstituted C1-C20 straight chain or branched alkyl, substituted or unsubstituted C3-C 20 Cycloalkyl, substituted or unsubstituted C6~C 30 Aryl, substituted or unsubstituted C3~C 20 One of heteroaryl, halogen or ester groups;

[0021] The general formula of the comonomer B is:

[0022] Formula III;

[0023] Wherein, R5, R6, R7, and R8 are hydrogen, substituted or unsubstituted C0~C20 straight chain or branched alkyl, substituted or unsubstituted C3~C 20 Cycloalkyl, substituted or unsubstituted C6~C 30 Aryl, substituted or unsubstituted C3~C 20 At least one of a heteroaryl group, a halogen group or an ester group;

[0024] a is 0, 1 or 2.

[0025] Preferably, the comonomer A is one of the following IIa~IIi;

[0026] .

[0027] Preferably, the comonomer B is one of the following IIIa~IIIo;

[0028] .

[0029] Preferably, the catalyst for the copolymerization reaction is a metallocene compound of a transition metal such as Ti, Zr, or Hf.

[0030] Further, the catalyst for the copolymerization reaction is Cp2ZrCl2, Me2SiCp2ZrMe2, Me2SiCp2ZrCl2, Me2SiCp2ZrEt2, Me2SiCp2ZrMeCl, Me2SiCp2ZrBr2, Me2(Ind)2ZrCl2, Me2Si(Ind)2ZrMe2, Me2Si(Ind)2ZrEt2, Et(Ind)2ZrCl2, (Ind)2ZrCl2, EtCp(Ind)ZrCl2, EtSi(Ind)2ZrCl2, EtCp(Flu)ZrCl2, EtSi(Flu)2ZrCl2, EtCp(Ind)HfCl2, (Ind)2ZrCl2, EtCp(Ind)2ZrCl2, EtCp(Flu)ZrCl2, EtSi(Flu)2ZrCl2, EtCp(Ind)HfCl2, EtCp(Ind)2ZrMe2, EtCp(Ind)2ZrEt2, EtCp(Ind)2ZrCl2, EtCp(Flu)2ZrCl2, EtCp(Flu)2ZrCl2, EtCp(Flu)2Zr d)2HfCl2, Ph2Cp(Ind)ZrCl2, Ph2Cp(Flu)ZrCl2, Et(Ind)2TiCl2, Me2SiCp2TiCl2, (Ind)2TiCl2, EtCp(Ind)TiCl2, EtCp(Flu)TiCl2, Ph2Cp(Flu)TiCl 2. Me2(Ind)2TiCl2, Me2Si(Ind)2HfCl2, Me2SiCp2HfCl2, Me2(Ind)2ZrCl2, EtCp(Flu)HfCl2, Ph2Cp(Ind)HfCl2, Ph2(Flu)2HfCl2, Ph2Cp(Flu)HfCl2, At least one of Me2(Ind)2HfCl2.

[0031] Preferably, the co-catalyst of the copolymerization reaction is at least one of trialkylaluminum, alkylaluminoxane (MAO) or organic boron compound, triethylaluminum, tripropylaluminum, triisopropylaluminum, tri-n-butylaluminum, triisobutylaluminum, tri-sec-butylaluminum, tri-tert-butylaluminum, tripentylaluminum, diethylethoxyaluminum, diethylaluminum monochloride, ethylaluminum dichloride, diethylaluminum bromide, diisobutylaluminum chloride, methylaluminumoxane (MAO), modified methylaluminumoxane (MMAO) or ethylaluminumoxane, cycloboroxane, triethylborane, triphenylborane, triphenylborane ammonia complex, NaBH4, tributyl borate, triisopropyl borate, tri(pentafluorophenyl)borane, dimethylphenylammonium tetra(pentafluorophenyl)borate, diethylphenylammonium tetra(pentafluorophenyl)borate, methyldiphenylammonium tetra(pentafluorophenyl)borate, and ethyldiphenylammonium tetra(pentafluorophenyl)borate.

[0032] Preferably, the solvent of the copolymerization reaction is at least one of toluene, xylene, n-hexane, n-heptane, cyclopentane, methylcyclopentane, cyclohexane, methylcyclohexane and cyclooctane;

[0033] The molecular regulator of the copolymerization reaction is at least one of hydrogen, dimethyl zinc, diethyl zinc, dipropyl zinc and diisobutyl zinc.

[0034] Preferably, the reaction temperature of the copolymerization reaction is 20-70° C., the reaction pressure is 2.0-30 bar, and the residence time is 5-50 min.

[0035] The technical solution adopted by the present invention to solve the third technical problem is: an application of the above-mentioned high refractive index cyclic olefin copolymer, characterized in that: the high refractive index cyclic olefin copolymer is used in the preparation of optical lenses / lenses, polarizing films, contact lenses or AR / VR.

[0036] Compared with the prior art, the advantages of the present invention are: the refractive index of the cycloolefin copolymer prepared by the present invention is 1.55-1.64, the transmittance is above 90%, the glass transition temperature is 79-190°C, the birefringence does not exceed 25nm, and it has a higher refractive index and higher transmittance, heat resistance, and lower birefringence, and is economically suitable for scaled-up production. DETAILED DESCRIPTION

[0037] The present invention is further described in detail below with reference to the embodiments.

[0038] Embodiment 1:

[0039] In a 100 ml reactor, the pressure was 10 bar. The system was first repeatedly evacuated and replaced with nitrogen three times at 500 ° C, and then replaced with ethylene three times, maintaining an ethylene flow rate of 2NL / hr, so that the entire reaction system reached the requirements of sealing, anhydrous and oxygen-free, and then the system temperature was set to 20 ° C;

[0040] Then, 8.0 g of the compound of formula IId and 2.0 g of the compound of formula IIIa, 103 ml of toluene, and 10 mL of hydrogen were added to the system. The catalyst used was Et(Ind)2TiCl2, 3.95 ml of a 10 μmol / L solution prepared with toluene, and the co-catalyst was MAO, 1.97 ml of a 1 mol / L solution prepared with toluene, wherein the molar ratio of titanium to aluminum was 1:500. After reacting for 20 minutes, methanol was injected to terminate the reaction.

[0041] Subsequently, 100 mL of an aqueous solution containing 10 wt % NaOH was added, and after stirring and washing in a water bath at 70° C., the polymer solution was washed with pure water until it became neutral, and ethanol was precipitated. The polymer was vacuum dried at 80° C. for more than 8 hours to obtain 26.2 g of a copolymer.

[0042] Embodiment 2:

[0043] The difference from Example 1 is that: the pressure is 15 bar; the ethylene flow rate is maintained at 10 NL / hr; 3 g of the compound of formula IId structure and 9 g of the compound of formula IIIa structure are used as comonomers; the catalyst is Et(Ind)2ZrCL2, which is prepared into a solution with a concentration of 10 μmol / L in toluene and 4.44 ml is taken; the cocatalyst is triethylaluminum, which is prepared into a solution with a concentration of 1 mol / L in toluene and 4.44 ml is taken; the solvent is 124 ml of toluene; the reaction temperature is 40°C; the reaction time is 15 min;

[0044] After polymerization treatment, 22.6 g of a copolymer was obtained.

[0045] Embodiment 3:

[0046] The difference from Example 1 is that: the pressure is 20 bar; the ethylene flow rate is maintained at 6 NL / hr; 5 g of the compound of formula IIa structure and 5 g of the compound of formula IIIa structure are used as comonomers; the catalyst is Et(Ind)2ZrCL2, which is prepared into a solution with a concentration of 10 μmol / L in toluene and 3.66 ml is taken; the co-catalyst is triethylaluminum, which is prepared into a solution with a concentration of 1 mol / L in toluene and 1.83 ml is taken; the solvent is 103 ml of toluene; the reaction temperature is 60°C; the reaction time is 25 min;

[0047] After polymerization treatment, 19.6 g of copolymer was obtained.

[0048] Embodiment 4:

[0049] The difference from Example 1 is that: the pressure is 15 bar; the ethylene flow rate is maintained at 1NL / hr; 5g of the compound of formula IId structure and 5g of the compound of formula IIIb structure are used as comonomers; the catalyst is Et(Ind)2ZrCL2; 4.93ml of a solution with a concentration of 10μmol / L prepared in toluene is taken; the cocatalyst is triethylaluminum, and 2.47ml of a solution with a concentration of 1mol / L prepared in toluene is taken; the solvent is 105ml of toluene; the reaction temperature is 40°C; the reaction time is 25min;

[0050] After polymerization treatment, 20.8 g of a copolymer was obtained.

[0051] Embodiment 5:

[0052] The difference from Example 1 is that: the pressure is 25 bar; the ethylene flow rate is maintained at 4NL / hr; 3g of the compound of formula IIc structure and 4.75g of the compound of formula IIIk structure are used as comonomers; the catalyst is Ph2Cp(Flu)ZrCl2, which is prepared into a 10μmol / L solution in toluene and 2.47ml is taken; the cocatalyst is MAO, which is prepared into a 1mol / L solution in toluene and 3.08ml is taken; the solvent is 133ml of toluene; the reaction temperature is 30°C; the reaction time is 10min;

[0053] After polymerization treatment, 18.6 g of copolymer was obtained.

[0054] Embodiment 6:

[0055] The difference from Example 1 is that: the pressure is 18 bar; the ethylene flow rate is maintained at 4NL / hr; 5 g of the compound of formula IIa structure and 2.02 g of the compound of formula IIId structure are used as comonomers; the catalyst is Ph2Cp(Flu)ZrCl2, which is prepared into a 10 μmol / L solution in toluene and 1.83 ml is taken; the cocatalyst is MAO, which is prepared into a 1 mol / L solution in toluene and 1.23 ml is taken; the solvent is 133 ml of toluene; the reaction temperature is 30°C; the reaction time is 30 min;

[0056] After polymerization treatment, 17.4 g of a copolymer was obtained.

[0057] Embodiment 7:

[0058] The difference from Example 1 is that: the pressure is 20 bar; the ethylene flow rate is maintained at 2NL / hr; 5 g of the compound of formula IIa structure and 2.79 g of the compound of formula IIId structure are used as comonomers; the catalyst is Ph2Cp(Flu)ZrCl2, which is prepared into a 10 μmol / L solution in toluene and 1.83 ml is taken; the cocatalyst is MAO, which is prepared into a 1 mol / L solution in toluene and 1.23 ml is taken; the solvent is 133 ml of toluene; the reaction temperature is 30°C; the reaction time is 30 min;

[0059] After polymerization treatment, 18.1 g of a copolymer was obtained.

[0060] Embodiment 8:

[0061] The difference from Example 1 is that: the pressure is 15 bar; the ethylene flow rate is maintained at 10 NL / hr; 3 g of the compound of formula IId structure and 9 g of the compound of formula IIIa structure are used as comonomers; the catalyst is Et(Ind)2ZrCL2, which is prepared into a solution with a concentration of 10 μmol / L in toluene and 4.44 ml is taken; the cocatalyst is triethylaluminum, which is prepared into a solution with a concentration of 1 mol / L in toluene and 4.44 ml is taken; the solvent is 124 ml of toluene; the reaction temperature is 80°C; the reaction time is 40 min;

[0062] After polymerization treatment, 5.15 g of a copolymer was obtained.

[0063] Embodiment 9:

[0064] The difference from Example 1 is that: the reaction pressure is 23 bar; the ethylene flow rate is maintained at 10 NL / hr; 3 g of the compound of formula IId structure and 9 g of the compound of formula IIIa structure are used as comonomers; the catalyst is Ph2Cp(Flu)ZrCl2, which is prepared into a 10 μmol / L solution in toluene and 4.4 ml is taken; the co-catalyst is MAO, which is prepared into a 1 mol / L solution in toluene and 4.4 ml is taken; the solvent is 103 ml of toluene; the reaction temperature is 10°C; the reaction time is 20 min;

[0065] After polymerization treatment, 13.9 g of a copolymer was obtained.

[0066] Embodiment 10:

[0067] The difference from Example 1 is that: the reaction pressure is 50 bar; the ethylene flow rate is maintained at 6 NL / hr; 10 g of the compound of formula IIa structure and 1.0 g of the compound of formula IIIa structure are used as comonomers; the catalyst is Ph2Cp(Flu)ZrCl2, which is prepared into a 10 μmol / L solution in toluene and 3.52 ml is taken; the cocatalyst is triethylaluminum, which is prepared into a 1 mol / L solution in toluene and 1.76 ml is taken; the solvent is 114 ml of toluene; the reaction temperature is 35°C; the reaction time is 30 min;

[0068] After polymerization treatment, 12.1 g of a copolymer was obtained.

[0069] Embodiment 11:

[0070] The difference from Example 1 is that: the pressure is 1.0 bar; the ethylene flow rate is maintained at 6 NL / hr; 6.0 g of the compound of formula IId and 6.28 g of the compound of formula IIIa are used as comonomers; the catalyst used is Et(Ind)2TiCl2, which is prepared into a solution with a concentration of 10 μmol / L in toluene and 8.8 ml is taken; the cocatalyst is MAO, which is prepared into a solution with a concentration of 1 mol / L in toluene and 9.7 ml is taken; the solvent is 126 ml of toluene; the reaction temperature is 20°C; the reaction time is 30 min;

[0071] After polymerization treatment, 13.6 g of copolymer was obtained.

[0072] Embodiment 12:

[0073] The difference from Example 1 is that: the pressure is 15.0 bar; the ethylene flow rate is maintained at 1.6 NL / hr; 5 g of the compound of formula IId and 5.23 g of the compound of formula IIIa are used as comonomers; the catalyst used is Et(Ind)2TiCl2, which is prepared into a solution with a concentration of 10 μmol / L in toluene and 7.4 ml is taken; the cocatalyst is MAO, which is prepared into a solution with a concentration of 1 mol / L in toluene and 7.4 ml is taken; the solvent is 106 ml of toluene; the reaction temperature is 20°C; the reaction time is 30 min;

[0074] After polymerization treatment, 4.8 g of a copolymer was obtained.

[0075] Embodiment 13:

[0076] The difference from Example 1 is that: the pressure is 30 bar; the ethylene flow rate is maintained at 8 NL / hr; 5.0 g of the compound of formula IIc structure and 6.51 g of the compound of formula IIIk structure are used as comonomers; the catalyst is Ph2Cp(Flu)ZrCl2, which is prepared into a 10 μmol / L solution in toluene and 4.11 ml is taken; the cocatalyst is MAO, which is prepared into a 1 mol / L solution in toluene and 4.52 ml is taken; the solvent is 119 ml of toluene; the reaction temperature is 30°C; the reaction time is 3 min;

[0077] After polymerization treatment, 3.6 g of copolymer was obtained.

[0078] Embodiment 14:

[0079] The difference from Example 1 is that: the pressure is 15 bar; the ethylene flow rate is maintained at 3NL / hr; 8 g of the compound of formula IIc structure and 2.59 g of the compound of formula IIIb structure are used as comonomers; the catalyst is Et(Ind)2ZrCL2, which is prepared into a solution with a concentration of 10 μmol / L in toluene and 3.59 ml is taken; the cocatalyst is triethylaluminum, which is prepared into a solution with a concentration of 1 mol / L in toluene and 1.79 ml is taken; the solvent is 110 ml of toluene; the reaction temperature is 40°C; the reaction time is 90 min;

[0080] After polymerization treatment, 10.2 g of a copolymer was obtained.

[0081] Comparative Example 1:

[0082] The difference from Example 1 is that: the pressure is 10 bar; the ethylene flow rate is maintained at 10 NL / hr; 10.0 g of the compound of formula IIIa structure and 5.19 g of the compound of formula IIIc structure are used as comonomers; the catalyst is Me2(Ind)2ZrCl2, which is prepared into a 10 μmol / L solution in toluene and 2.35 ml is taken; the cocatalyst is MAO, which is prepared into a 1 mol / L solution in toluene and 3.39 ml is taken; the solvent is 90 ml of toluene; the reaction temperature is 20°C, and the reaction time is 25 min;

[0083] After polymerization treatment, 15.7 g of a copolymer was obtained.

[0084] Comparative Example 2:

[0085] The difference from Example 1 is that: the pressure is 20 bar; the ethylene flow rate is maintained at 3NL / hr; 10.0g of the compound of formula IIa structure is used as the comonomer; the catalyst is Et(Ind)2TiCl2, which is prepared into a solution with a concentration of 10μmol / L in toluene and 2.46ml is taken; the co-catalyst is trimethylaluminum, which is prepared into a solution with a concentration of 1mol / L in toluene and 1.23ml is taken; the solvent is 104ml of toluene; the reaction temperature is 20°C; the reaction time is 30min;

[0086] After polymerization treatment, 15.9 g of a copolymer was obtained.

[0087] The performance test results of the copolymers prepared in all the above embodiments and comparative examples are shown in Table 1.

[0088] Table 1:

[0089]

[0090] The specific test steps are as follows:

[0091] (1) x, y, z: The structure of the prepared polymer was determined using a nuclear magnetic resonance spectrometer (NMR, Bruker 400 MHz) at 25 °C with deuterated chloroform (CDCl3) as solvent and tetramethylsilane (TMS) as internal standard;

[0092] (2) Activity: polymer reaction activity = polymer produced by the reaction (including copolymers and insoluble matter) kg / (molar amount of catalyst used mmol) × residence time h;

[0093] (3) Glass transition temperature (Tg): measured by TAInstruments DSC25; 5.0-7.0 mg of polymer sample was taken, heated to 260°C at 40°C / min, kept constant for 5 min to eliminate thermal history, then cooled to 40°C at 20°C / min, kept constant for 5 min, and then heated to 260°C at 20°C / min. The glass transition temperature of the polymer was obtained from the second heating curve;

[0094] (4) Refractive index: measured by ATAGO DR-M2 Abbe refractometer. The polymer was molded into a 20 mm*7 mm*3 mm long sheet and tested under a standard D light source at 589 nm to obtain the Abbe number and refractive index.

[0095] (5) Birefringence: measured by SE-VE-L ellipsometer. The polymer was molded into a disc with a diameter of 25 mm and a thickness of 1 mm. The birefringence was measured directly at an incident angle of 65° under a circular spot using a standard wavelength range of 380 to 1000 nm.

[0096] (6) Light transmittance: measured by a HAM-200 haze meter. The polymer was molded into a disc with a diameter of 25 mm and a thickness of 1 mm. The light transmittance was measured under a standard C light source with a wavelength of 380-780 nm.

[0097] From Table 1 we can see that:

[0098] (1) The cycloolefin copolymer prepared in the embodiment of the present invention has a refractive index of 1.55-1.64, a transmittance of more than 90%, a glass transition temperature of 113.6-178.3°C, and a birefringence of no more than 23.3nm. It has high refractive index and high transmittance, heat resistance, and low birefringence.

[0099] (2) By comparing Example 1 with Examples 8-9, it can be seen that the reaction activity first increases and then decreases as the reaction temperature increases, because increasing the temperature is conducive to overcoming the difference in conformational energy between the four-membered ring intermediate state and the π complex during ethylene polymerization, thereby increasing the polymerization reaction rate constant. When the temperature increases, the dissolved ethylene in the system will gradually decrease, and the decrease in the concentration of reactants will lead to a decrease in the activity of the reaction system;

[0100] (3) By comparing Example 1 and Examples 10-11, it can be seen that the reaction activity first increases and then decreases with the increase of reaction pressure. When the pressure increases, the concentration of dissolved ethylene increases, and the ethylene participating in the reaction in the product increases. The reaction activity increases when the ethylene increases at the beginning. When the amount of ethylene reaches a certain level and the amount of the comonomer decreases, the reaction activity decreases.

[0101] (4) By comparing Example 1 and Example 12, it can be seen that when the molar ratio of ethylene in the polymer is less than 35%, the reaction activity decreases. The reason is that the steric hindrance of the copolymer monomer A is large. When the molar ratio of ethylene is less than 35%, the steric hindrance of the reaction increases, resulting in a decrease in the reaction activity;

[0102] (5) By comparing Example 1 with Examples 13-14, it can be seen that when the residence time is short, the reaction rate is fast and the reaction exotherm is intense; increasing the residence time can allow the reactants and the catalyst to react fully and increase the reaction yield; when the residence time is too long, the amount of monomer A in the reaction system decreases, resulting in a decrease in reaction activity;

[0103] (6) By comparing Example 1 with Comparative Example 1, it can be seen that the refractive index of the cycloolefin copolymer obtained by using the copolymer monomers A and B provided by the present invention for polymerization is 1.64 and the transmittance is 92.0%. The reason is that: both the copolymer monomers A and B have benzene ring structures, and the increase of benzene ring structures can increase the refractive index of the polymer;

[0104] (7) By comparing Example 1 and Comparative Example 2, it can be seen that when only comonomer A and α-olefin are polymerized, the refractive index of the obtained cycloolefin copolymer is 1.56, and the activity and transmittance are relatively low. The reason is that when only comonomer A and α-olefin are polymerized, the steric hindrance of comonomer A is relatively large during the polymerization reaction, resulting in low activity and transmittance.

Claims

1. A high refractive index cycloolefin copolymer, characterized in that The general formula is: Formula I; Wherein, R1, R2, R3, R4, R5, R6, R7, and R8 are hydrogen, substituted or unsubstituted C1-C20 straight chain or branched alkyl, substituted or unsubstituted C3-C 20 Cycloalkyl, substituted or unsubstituted C6~C 30 Aryl, substituted or unsubstituted C3~C 20 One of heteroaryl, halogen or ester groups; a is 0, 1 or 2; The molar ratio of x, y, and z is (5~40%):(35~85%):(5~65%).

2. The high refractive index cyclic olefin copolymer according to claim 1, characterized in that: R1, R2, R3, R4, R5, R6, R7, R8 are -H, -(CH2)n-R9, -(CH2)nOR 10 、-(CH2)nSR 11 、C1~C 12 Straight chain, C5~C 15 Cycloalkyl, C6~C 20 Aryl, C3~C 15 One of the heteroaryl groups or ester groups, n is an integer from 1 to 16; Among them, R9, R 10 , R 11 It is one of hydrogen, biphenyl, naphthyl, carbazole, fluorenyl, acenaphthenyl, phenanthryl and diphenylamino.

3. The high refractive index cyclic olefin copolymer according to claim 1, characterized in that: The high-refractive-index cycloolefin copolymer has a refractive index of 1.55-1.64, a light transmittance of more than 90%, a glass transition temperature of 79-190° C., and a birefringence of no more than 25 nm.

4. A method for preparing a high refractive index cyclic olefin copolymer according to any one of claims 1 to 3, characterized in that The method comprises the following steps: copolymerizing comonomer A, comonomer B and ethylene to obtain the high refractive index cycloolefin copolymer; The general formula of the comonomer A is: Formula II; Wherein, R1, R2, R3, and R4 are hydrogen, substituted or unsubstituted C1-C20 straight chain or branched alkyl, substituted or unsubstituted C3-C 20 Cycloalkyl, substituted or unsubstituted C6~C 30 Aryl, substituted or unsubstituted C3~C 20 One of heteroaryl, halogen or ester groups; The general formula of the comonomer B is: Formula III; Wherein, R5, R6, R7, and R8 are hydrogen, substituted or unsubstituted C0~C20 straight chain or branched alkyl, substituted or unsubstituted C3~C 20 Cycloalkyl, substituted or unsubstituted C6~C 30 Aryl, substituted or unsubstituted C3~C 20 At least one of a heteroaryl group, a halogen group or an ester group; a is 0, 1 or 2.

5. The preparation method according to claim 4, characterized in that: The comonomer A is one of the following IIa~IIc, IIe~IIi; 。 6. The preparation method according to claim 4, characterized in that: The comonomer B is one of the following IIIa~IIId, IIIf, IIIk~IIIl, IIIm, IIIo; 。 7. The preparation method according to claim 4, characterized in that: The catalyst for the copolymerization reaction is a metallocene catalyst; The co-catalyst of the copolymerization reaction is at least one of triethylaluminum, tripropylaluminum, triisopropylaluminum, tri-n-butylaluminum, triisobutylaluminum, tri-sec-butylaluminum, tri-tert-butylaluminum, tripentylaluminum, diethylethoxyaluminum, diethylaluminum monochloride, ethylaluminum dichloride, diethylaluminum bromide, diisobutylaluminum chloride, methylaluminoxane, modified methylaluminoxane or ethylaluminoxane, boroxane, triethylborane, triphenylborane, triphenylborane ammonia complex, NaBH4, tributyl borate, triisopropyl borate, tri(pentafluorophenyl)borane, dimethylphenylammonium tetra(pentafluorophenyl)borate, diethylphenylammonium tetra(pentafluorophenyl)borate, methyldiphenylammonium tetra(pentafluorophenyl)borate, and ethyldiphenylammonium tetra(pentafluorophenyl)borate.

8. The preparation method according to claim 4, characterized in that: The solvent of the copolymerization reaction is at least one of toluene, xylene, n-hexane, n-heptane, cyclopentane, methylcyclopentane, cyclohexane, methylcyclohexane and cyclooctane; The molecular regulator of the copolymerization reaction is at least one of hydrogen, dimethyl zinc, diethyl zinc, dipropyl zinc and diisobutyl zinc.

9. The preparation method according to claim 4, characterized in that: The reaction temperature of the copolymerization reaction is 20-70° C., the reaction pressure is 2.0-30 bar, and the residence time is 5-50 min.

10. An application of the high refractive index cyclic olefin copolymer according to any one of claims 1 to 3, characterized in that: The high refractive index cyclic olefin copolymer is used in the preparation of optical lenses / lenses, polarizing film, contact lenses or AR / VR.

Citation Information

Patent Citations

  • Method for preparing cycloolefin copolymer by adopting continuous flow integrated microreactor

    CN117362502A

  • Cycloolefin copolymer and preparation method thereof

    CN118027264A